2000
DOI: 10.4049/jimmunol.165.7.3934
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Effects of Surfactant Protein A or D Deficiency During Bacterial Infection on the Lung

Abstract: Mice lacking surfactant protein (SP)-A (SP-A−/−) or SP-D (SP-D−/−) and wild-type mice were infected with group B streptococcus or Haemophilus influenzae by intratracheal instillation. Although decreased killing of group B streptococcus and H. influenzae was observed in SP-A−/− mice but not in SP-D−/− mice, deficiency of either SP-A or SP-D was associated with increased inflammation and inflammatory cell recruitment in the lung after infection. Deficient uptake of bacteria by alveolar macrophages was observed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
276
4
12

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(306 citation statements)
references
References 30 publications
14
276
4
12
Order By: Relevance
“…[29][30][31] Plasma levels and functional activity of the collectins are known to be determined by polymorphisms in exon 1 and in the promotor region of the MBL2 gene, and thus a genetic susceptibility to the development of severe infections has been suggested as genetic variants associated with low MBL concentrations revealed a clinical phenotype. 3,[7][8][9][10] Preterm infants, known to exhibit a markedly increased risk for the development of severe infections, may critically depend on their innate immune response, as the presence of early-onset and nosocomial infections mainly determines acute and long-term morbidity and mortality in this population, especially regarding the development of neurological and pulmonary impairment.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] Plasma levels and functional activity of the collectins are known to be determined by polymorphisms in exon 1 and in the promotor region of the MBL2 gene, and thus a genetic susceptibility to the development of severe infections has been suggested as genetic variants associated with low MBL concentrations revealed a clinical phenotype. 3,[7][8][9][10] Preterm infants, known to exhibit a markedly increased risk for the development of severe infections, may critically depend on their innate immune response, as the presence of early-onset and nosocomial infections mainly determines acute and long-term morbidity and mortality in this population, especially regarding the development of neurological and pulmonary impairment.…”
Section: Discussionmentioning
confidence: 99%
“…SP-D связывается с грамотрицательными бактериями, такими как Pseudomonas aeruginosa, Klebsiella pneumoniae, Escherichia coli и Haemophilus influenzaе, способствуя их агглютинации и стимуляции хемотак-сиса нейтрофилов, макрофагов и эозинофилов к месту инвазии патогена [25][26][27]. SP-D также может связываться с грамположи-тельными бактериями, такими как Streptococcus pneumoniae и Stafylococcus aureus, а также с микобактериями [28,29], респира-торно-синцитиальным вирусом, вирусом гриппа [30], грибами Pneumocystis carinii, Aspergillus fumigatus, Cryptococcus neoformans, Candida albicans [31].…”
Section: терапевтический архив 1 2015unclassified
“…SP-A (-/-) мыши проявляли повышенную чувстви-тельность к ряду патогенных микроорганизмов, включая группу Streptococcus [35], P aeruginosa [36], H. influenza [27], P carinii [37,38], K. pneumonia [34]. SP-D (-/-) мыши более восприимчивы к инфекциям дыхательных путей, вызываемым вирусом гриппа [17], респираторно-синцитиальным вирусом [28].…”
Section: терапевтический архив 1 2015unclassified
“…Surfactant blocks lipopolysaccharide (LPS) signaling and inhibits proinflammatory cytokine secretion in human alveolar macrophages [12,13], and deficiency of surfactant protein increases the inflammatory response to LPS in vitro [14,15]. Several experimental and clinical studies indicated that surfactant proteins attenuate acute lung injury and/or production of inflammatory cytokines in the lungs [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%